Design, synthesis and biological profiling of bis-thiazole linked Schiff bases as effective enzyme inhibitors for targeting urease and thymidine phosphorylase proteins - Yousaf Khan; Hina Sarfraz; Mahrukh Naseem; Rubina Adnan; Syeda Farwa Naqvi; Azmatullah Khan; Urooba Gulshan; Syed Aminullah (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Further evidence of biallelic NAV3 variants associated with recessive neurodevelopmental disorder with dysmorphism, developmental delay, intellectual disability, and behavioral abnormalities - Naseebullah Kakar; Selinda Mascarenhas; Asmat Ali; Azmatullah; Syed M. Ijlal Haider; Vaishnavi Ashok Badiger; Mobina Shadman Ghofrani; Nathalie Kruse; Sohana Nadeem Hashmi; Jelena Pozojevic; Saranya Balachandran; Mathias Toft; et al. (Human Genetics, 2025)
Neuron navigators (NAVs) are cytoskeleton-associated proteins well known for their role in axonal guidance, neuronal migration, and neurite growth necessary for neurodevelopment. Neuron navigator 3 (NAV3) is one of the three NAV proteins highly expressed in the embryonic and adult brain. However, the role of the NAV3 gene in human disease is not well-studied. Recently, five bi-allelic and three mono-allelic variants in NAV3 were reported in 12 individuals from eight unrelated families with neurodevelopmental disorder (NDD). Here, we report five patients from three unrelated consanguineous families segregating autosomal recessive NDD. Patients have symptoms of dysmorphism, intellectual disability, developmental delay, and behavioral abnormalities. Exome sequencing (ES) was performed on two affected individuals from one large family, and one affected individual from each of the other two families. ES revealed two homozygous nonsense c.6325C > T; p.(Gln2109Ter) and c.6577C > T; p.(Arg2193Ter) and a homozygous splice site (c.243 + 1G > T) variants in the NAV3 (NM_001024383.2). Analysis of single-cell sequencing datasets from embryonic and young adult human brains revealed that NAV3 is highly expressed in the excitatory neurons, inhibitory neurons, and microglia, consistent with its role in neurodevelopment. In conclusion, in this study, we further validate biallelic protein truncating variants in NAV3 as a cause of NDD, expanding the spectrum of pathogenic variants in this newly discovered NDD gene.

Advancements and prospects in the utilization of metal ions and polymers for enhancing aerobic granulation during industrial effluent treatment and resource recovery - Ahmad Hussaini Jagaba; Dahiru U. Lawal; Ismail Abdulazeez; Ibrahim Mohammed Lawal; Nuhu Dalhat Mu'azu; Abdullahi Haruna Birniwa; Abdullahi Kilaco Usman; Haithm Salah Hagar; Nura Shehu Aliyu Yaro; Azmatullah Noor; Kunmi Joshua Abioye; Jun Wei Lim; et al. (Journal of Water Process Engineering, 2024)

A review on the application of biochar as an innovative and sustainable biocarrier material in moving bed biofilm reactors for dye removal from environmental matrices - Ahmad Hussaini Jagaba; Ismail Abdulazeez; Dahiru U. Lawal; Augustine Chioma Affam; Nuhu Dalhat Mu’azu; Usman Bala Soja; Abdullahi Kilaco Usman; Azmatullah Noor; Jun Wei Lim; Isam H. Aljundi (Environmental Geochemistry and Health, 2024)

Treatment of petrochemical wastewater by 3D printed biocarrier integrated activated sludge system: Optimization by response surface methodology, biokinetics, and microbial community - Azmatullah Noor; Wahid Ali; Tarique Ahmad; Md. Tabish Noori; Shams Anwar; Mohammad Ehtisham Khan; Augustine Chioma Affam; Abdullateef H. Bashiri; Waleed Zakri; Ahmad Hussaini Jagaba (Journal of Water Process Engineering, 2023)

Trend and current practices of coagulation-based hybrid systems for pulp and paper mill effluent treatment: mechanisms, optimization techniques and performance evaluation - Ahmad Hussaini Jagaba; Abdullahi Haruna Birniwa; Abdullahi Kilaco Usman; Nuhu Dalhat Mu'azu; Nura Shehu Aliyu Yaro; Usman Bala Soja; Kunmi Joshua Abioye; Najib Mohammed Yahya Almahbashi; Baker Nasser Saleh Al-dhawi; Azmatullah Noor; Ibrahim Mohammed Lawal (Journal of Cleaner Production, 2023)

Biochar-based geopolymer nanocomposite for COD and phenol removal from agro-industrial biorefinery wastewater: Kinetic modelling, microbial community, and optimization by response surface methodology - Ahmad Hussaini Jagaba; Ibrahim Mohammed Lawal; Ayman A. Ghfar; Abdullahi Kilaco Usman; Nura Shehu Aliyu Yaro; Azmatullah Noor; Kunmi Joshua Abioye; Abdullahi Haruna Birniwa (Chemosphere, 2023)

The adsorptive removal of lead ions in aquatic media: Performance comparison between advanced functional materials and conventional materials - Botao Liu; Azmatullah Khan; Ki-Hyun Kim; Deepak Kukkar; Ming Zhang (Critical Reviews in Environmental Science and Technology, 2020)